(untitled) - Pence, Gregory E. (New York, 1995)
This collection provides an in depth look at the real cases defining the field of medical ethics. A popular text among teachers and students alike, the book contains much more detail than most other casebooks, enriching each famous (or infamous) case with important background, history and context. In addition, it illuminates each case with a discussion of the pertinent philosophical theories and ethical issues behind it. The second edition has been substantially changed and updated, with three completely new chapters and significant revision to all of the other chapters.
Keywords: Medical ethics; Case studies